Sustainable Campus: Indoor Environmental Quality (IEQ) Performance Measurement for Malaysian Public Universities - Wan Yusoff, Wan Zahari; Azwan Sulaiman, Muhammad (European Journal of Sustainable Development, 2014)
Indoor Environmental Quality (IEQ) for academic buildings is one of the key characteristics of a sustainable campus. The low conditions of IEQ performance can contribute to the sick building syndrome and cause discomfort to the building users. Furthermore, good performance of IEQ can contribute to a comfort and conducive learning and working environment. The purpose of this paper is to discuss on the IEQ performance measurement of academic buildings for public universities in Malaysia. This research involved scientific measurement of academic buildings for public universities in Malaysia. The performance measurement focuses on the six key elements of IEQ; thermal comfort, humidity, noise comfort, air movement, lighting and thickness of CO2. The results were compared to the Malaysian Standard (MS 1525:2007) and UNESCO guideline. The findings showed that most universities are in the standard set, while some universities under the standards set and still in need of improvement. This study is useful for facilities managers in public universities in order to improve the IEQ on academic buildings in achieving sustainable campus. Keywords: Sustainable development, Sustainable environment, Sustainable campus, Indoor Environmental Quality, Malaysian public universities.